Quality of life of post-menopausal women residing in rural and urban areas of Sikkim, India - Devi, Barkha; Karki, Prerna; Chhetry, Rajnee; Sharma, Neelam; Niroula, Manisha; Lepcha, Pema Chuki; Pradhan, Shobna; Sherpa, Yanchen; Sherpa, Anjali; Sharma, Priya; Sharma, Beenu; Thapa, Khushboo; et al. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Menopause is an inevitable reproductive phase during midlife when various physical and mental changes may impair the quality of life of women. The presence and severity of symptoms vary tremendously from woman to woman and can last from months to years during this transitional period. This study was conducted to assess the quality of life and menopause related problems among post-menopausal women residing rural and urban areas of Sikkim. Methods: Descriptive explorative study was done in East Sikkim among 120 rural and urban post-menopausal women who were in the age group of 45 years and above, had attained natural menopause and didn’t have menstruation from last one year, were selected through purposive sampling technique. Women with induced menopause, hysterectomy, receiving hormonal treatment were excluded. Along with collection of socio-demographic data, the Menopause Specific Quality of Life Questionnaire was used to assess the Quality of life based on experience of the symptoms through interview technique. Results: The mean menopausal age was 48±3.649 years in rural area and 47±3.831 years for urban area. The mean scores in quality of life between post-menopausal women in rural areas (M=136.6, SD=28.78) were found significantly impaired and the difference was found statistically significant (t=5.75 p<0.001) which shows that rural women were having impaired quality of life as compared to urban women during post-menopausal period. The findings also revealed that factors affecting the quality of life of postmenopausal women were the history of menopause, occupation of women, in urban women and time of attending menopause, in rural women. Conclusions: The present study shows that menopause related symptoms had a negative effect on the quality of life of the post-menopausal women. Such studies can help in creating awareness and in educating women on the early identification of the common menopausal symptoms.